2021
DOI: 10.1186/s12871-021-01378-7
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium release and fluid warming: provocational setting and devices at risk

Abstract: Background Fluid warming, recommended for fluid rates of > 500 ml h-1, is an integral part of patient temperature management strategies. Fluid warming devices using an uncoated aluminium containing heating element have been reported to liberate aluminium resulting in critical aluminium concentrations in heated fluids. We investigated saline solution (0.9%), artificially spiked with organic acids to determine the influence of fluid composition on aluminium release using the uncoated enFlow® d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…However, it is known that these types of hyperthermia devices and fluid warming devices have been withdrawn from the market and restricted in human use due to the risk of heavy metal poisoning, especially when the heated fluid comes into direct contact with the heater, such as aluminum, as stated in a bulletin issued by the FDA in 2021. [ 12 - 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that these types of hyperthermia devices and fluid warming devices have been withdrawn from the market and restricted in human use due to the risk of heavy metal poisoning, especially when the heated fluid comes into direct contact with the heater, such as aluminum, as stated in a bulletin issued by the FDA in 2021. [ 12 - 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…15 The newer cartridge has been extensively tested in a bench environment for the release of aluminum, other potentially toxic elements, and organic molecules with favorable results. 16 22 Additional bench testing also confirmed that the newer parylene-coated enFlow design warmed fluids as efficiently as the previous design; however, the performance of the parylene-coated enFlow has not been evaluated in a clinical setting. 16 …”
Section: Introductionmentioning
confidence: 89%
“…15 The newer cartridge has been extensively tested in a bench environment for the release of aluminum, other potentially toxic elements, and organic molecules with favorable results. [16][17][18][19][20][21][22] Additional bench testing also confirmed that the newer parylene-coated enFlow design warmed fluids as efficiently as the previous design; however, the performance of the parylene-coated enFlow has not been evaluated in a clinical setting. 16 To further assess this improved design in a clinical setting, this trial evaluated the efficacy of the new parylenecoated enFlow IV fluid and blood warming system in maintaining normothermia in patients undergoing surgery.…”
Section: Verification Of An Intravenous Fluid Warmer: a Prospective T...mentioning
confidence: 99%
“…9 Numerous previous studies have documented concerns over aluminum leaching from fluid warmers. 5,9,11 17…”
Section: Introductionmentioning
confidence: 99%
“…9 Numerous previous studies have documented concerns over aluminum leaching from fluid warmers. 5,9,[11][12][13][14][15][16][17] In addition to aluminum, the FDA has established Permitted Daily Exposures (PDEs) for all elements of toxicological concern within finished drug products. 18 The FDA considers daily exposure below these PDE levels to be protective of public health for all patient populations and is established for three different routes of administration: oral, parenteral, and inhalational.…”
Section: Introductionmentioning
confidence: 99%